2015
DOI: 10.4084/mjhid.2015.027
|View full text |Cite
|
Sign up to set email alerts
|

Age-Standardized Incidence Rates for Leukemia Associated With Consanguineous Marriages in 68 Countries, an Ecological Study

Abstract: Consanguineous marriage that defines as a union between biologically related persons has a variety of known deleterious correlations with factors that affect public health within human populations. To investigate the association between the mean of inbreeding coefficient (α) and incidence of leukemia, the present ecological study on 68 countries was carried out. Statistical analysis showed that the age-standardized incidence rate of leukemia positively correlated with log10GNI per capita (r=0.699, df=66, P<0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…It's clear in the chart figure the patients which there is no consanguinity between their parents have a great percentage (85%) while the patients which their parents were relatives of each other show a low percentage (15%), this result is similar with results were obtained by (Saadat, 2015) who concluded from the study (Age-standardized Incidence Rates for Leukemia Associated with Consanguineous Marriages in 68 Countries) that Leukemia rates are smaller in nations where consanguineous marriages are highly prevalent.…”
Section: The Distribution Of Patients With Chronic Myeloidsupporting
confidence: 85%
“…It's clear in the chart figure the patients which there is no consanguinity between their parents have a great percentage (85%) while the patients which their parents were relatives of each other show a low percentage (15%), this result is similar with results were obtained by (Saadat, 2015) who concluded from the study (Age-standardized Incidence Rates for Leukemia Associated with Consanguineous Marriages in 68 Countries) that Leukemia rates are smaller in nations where consanguineous marriages are highly prevalent.…”
Section: The Distribution Of Patients With Chronic Myeloidsupporting
confidence: 85%
“…The study demonstrated a very high level of consanguineous marriage among Iranian Mandaeans. It has been shown that consanguinity significantly increases the prevalence of inherited autosomal recessive diseases and many multifactorial traits such as infertility, congenital disorders, and mental retardation (Bittles et al, 1993;Bittles & Neel, 1994;Stoltenberg et al, 1999;Bittles, 2001;Saadat & Zendeh-Boodi, 2006;Saadat, 2008a;Tadmouri et al, 2009;Mansour et al, 2010;Saadat & Vakili-Ghartavol, 2010;Nafissi et al, 2010Nafissi et al, , 2011Anvar et al, 2011;Saadat, 2011Saadat, , 2015a. The harmful consequences of consanguineous mating emphasize the need for genetic counselling in the Mandaean community and the importance of preventive action to raise awareness about the risks of consanguinity.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that consanguinity results in homozygosity in offspring, it is associated with an elevation in the risk of autosomal recessive disease and several multifactorial complex traits (Bittles & Neel, 1994;Stoltenberg et al, 1999;Bittles, 2001;Saadat & Zendeh-Boodi, 2006;Saadat, 2008a;Tadmouri et al, 2009;Mansour et al, 2010;Saadat & Vakili-Ghartavol, 2010;Nafissi et al, 2010Nafissi et al, , 2011Anvar et al, 2011;Saadat, 2011Saadat, , 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that genetic components are involved in increasing the risk of developing leukemia. For this reason, the familial relationship of parents increases the children's homozygosity and increases the risk of cancer (27). Mehrvar et al reported that 41% of parents of children with leukemia had a familial relationship (28) and Bener et al's study showed the rate of leukemia and lymphoma in children of parents with a familial relationship was higher than in the unrelated group (29).…”
Section: Discussionmentioning
confidence: 99%